TYPES AND DENSITY OF SEAGRASS IN THE GENTING BEACH, TANJUNG MEDANG VILLAGE, RUPAT UTARA DISTRICT, BENGKALIS REGENCY, RIAU PROVINCE - Hidayah, Haini; Fauzi, Muhammad; Adriman, Adriman (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2019)
Seagrass is present in the Genting Beach. During the low tide, however, propeler of fishermen ship damage the seagrass habitat in general. To understand the types and density of seagrass in Genting Beach, a study has been conducted in April – June 2018. There were 3 sampling points, in the river mouth of the Genting River (SP I), in the shipping line (SP II), and in the mangrove area (SP III). Seagrass were taken from 3 quadrants (1x1 m) in each sampling point. Sampling were conducted once. The seagrass was then identified. Results shown that there was one type of seagrass species, namely Enhalus acoroides. Seagrass density range from 17.99 – 90.78 organism/m2 and the coverage of seagrass was around 3.04% – 14.39%, water temperature was 31.66 - 32ºC, salinity 32‰, pH 8, clarity 0.26 – 0.33 m, current flow 0.37 – 0.42 m/s, sandy mud substrate, nitrate 0.033 – 0.075 mg/L, phosphate 0.035 – 0.104 mg/L and organic material was 20.50 – 27.57%. The seagrass density in the Genting Beach is classified as rare and the coverage as low.